Questions to Heaven. Issue 6 (1st December 2021) - Fernando, Benjamin; Wójcicka, Natalia; Han, Zhanwen; Stott, Alexander; Ceylan, Savas; Charalambous, Constantinos; Collins, Gareth S; Estévez, Daniel; Froment, Marouchka; Golombek, Matthew; Gülzow, Peter; Horleston, Anna; et al.
Abstract : Benjamin Fernando and colleagues report on the international cooperation involved InSight's attempt to gather seismic data from the arrival at Mars of China's Zhurong rover. Abstract: Benjamin Fernando and colleagues report on the international cooperation involved InSight's attempt to gather seismic data from the arrival at Mars of China's Zhurong rover.